Physical mechanisms involved in the formation and operation of memory devices based on a monolayer of gold nanoparticle-polythiophene hybrid materials. Issue 7 (12th June 2019) - Zhang, T.; Guérin, D.; Alibart, F.; Troadec, D.; Hourlier, D.; Patriarche, G.; Yassin, A.; Oçafrain, M.; Blanchard, P.; Roncali, J.; Vuillaume, D.; Lmimouni, K.; et al.
Abstract : Understanding the physical and chemical mechanisms occurring during the forming process and operation of an organic resistive memory device is a requisite for better performance. Abstract : Understanding the physical and chemical mechanisms occurring during the forming process and operation of an organic resistive memory device is a requisite for better performance. Various mechanisms were suggested in vertically stacked memory structures, but the analysis remains indirect and needs destructive characterization ( e.g. analysis of the cross-section to access the organic layers sandwiched between electrodes). Here, we report a study on a planar, monolayer thick, hybrid nanoparticle/molecule device (10 nm gold nanoparticles embedded in an electro-generated poly(2-thienyl-3, 4-(ethylenedioxy)thiophene) layer), combining in situ physical (scanning electron microscopy, physicochemical thermogravimetry and mass spectroscopy, and Raman spectroscopy) and electrical (temperature dependent current–voltage) characterization on the same device. We demonstrate that the forming process causes an increase in the gold particle size, almost 4 times larger than the starting nanoparticles, and that the organic layer undergoes a significant chemical rearrangement from an sp 3 to sp 2 amorphous carbon material. Temperature dependent electrical characterization of this nonvolatile memory confirms that the charge transport mechanism in the device is consistent with a trap-filled space charge limited current in the off state, with the sp 2 amorphous carbon material containing many electrically active defects.